Executive function, repetitive behaviour and restricted interests in neurodevelopmental disorders. (March 2022) - Perry, Victoria; Ellis, Katherine; Moss, Jo; Beck, Sarah R.; Singla, Gursharan; Crawford, Hayley; Waite, Jane; Richards, Caroline; Oliver, Chris
Graphical abstract: Highlights: EF impairments may underpin RRBs in people with genetic syndromes and AUT people. People with CdLS, FXS and RTS, and AUT people showed impaired EF behaviours. Different EF behaviours predicted RRBs in each syndrome group. No associations between EF behaviour and RRBs were found in the AUT group. EF behaviours and RRBs may be influenced differently by context per syndrome group. Abstract: Background: Individuals with genetic syndromes show unique profiles of repetitive behaviours and restricted interests (RRBs). The executive dysfunction account of RRBs suggests that in autistic (AUT) individuals executive function impairments underpin RRBs, but not communication and social interaction autistic characteristics. Aims: To 1) describe profiles of behavioural manifestations of executive function (EF behaviours) and 2) explore the relationship between EF behaviours and autistic traits across individuals with Cornelia de Lange (CdLS), fragile X (FXS) and Rubinstein-Taybi syndromes (RTS), and AUT individuals. Method: Carers completed the Behavior Rating Inventory of Executive Function – Preschool Version and the Social Communication Questionnaire. Data reporting on 25 individuals with CdLS (Mage = 18.60, SD = 8.94), 25 with FXS (Mage = 18.48, SD = 8.80), 25 with RTS (Mage = 18.60, SD = 8.65) and 25 AUT individuals (Mage = 18.52, SD = 8.65) matched on chronological age and adaptive ability were included in analyses. Results: All groups showed impairments across EF behaviours compared to two-to-three-year-old typically developing normative samples with no differences between groups. Different EF behaviours predicted RRBs in the syndrome groups with no associations found in the AUT group. Conclusions: Syndrome related differences should be considered when developing targeted interventions that focus on EF behaviours and/or RRBs in these groups.